Translational control of transposition activity of the bacterial insertion sequence IS1. - Escoubas, J M (1991)
The experiments reported here provide strong evidence indicating that the transposition frequency of the bacterial insertion sequence IS1 is determined principally by two IS1-specified proteins. The first, InsA, was previously shown to bind to the ends of the element and to act as a repressor. We present both physical and genetic evidence which reveals that the second, the InsAB' transposase, is a fusion of InsA with the product of a downstream reading frame, InsB'. Synthesis of this protein occurs by a -1 frameshift between the insA and insB' frames. It requires the presence of an intact retroviral-like frameshift signal composed of an A6C motif and a downstream region able to form several alternative secondary structures. In vivo studies show that IS1 transposition activity depends on the relative rather than on the absolute levels of InsA and InsAB'. The ratio is determined primarily at the translational level by frameshifting and appears to be relatively insensitive to large variations in levels of transcription. This novel homeostatic control could therefore protect IS1 from activation as a consequence of insertion into active transcription units.